Nanomaterials for Eco-friendly Applications - Kopp Alves, Annelise; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents a wide range of synthesis and characterization techniques to produce ceramic nanomaterials specially developed to be used in environmental applications. The book cover synthesis using hydrothermal, chemical vapor deposition, sol-gel, emulsification, magneto-sputtering, among other process and modern characterization techniques with detail. The use of the synthesized materials in eco-friendly approaches such as photocatalysis, solar energy efficiency improvement, absorbents, sensors, solar cells, biofuels and waste reuse are reported in detail.
Cnt Sponges for Environmental Applications -- Electrolytic Conversion of Co2 to Carbon Nanostructures -- Tio2/Cnt Nanocomposites for Water Splitting Applications -- Tio2 Nanotubes as Photocatalyst for Biodiesel Production -- Metal Decoration of Tio2 Nanotubes for Photocatalytic and Water Splitting Applications -- Organic-Inorganic Hybrid Perovskites for Solar Cells Applications -- Rare-Earth Doped Forsterite: Anti-Reflection Coating with Upconversion Properties as Solar Capture Solution -- Chitin Adsorbents to Wastewater Treatment -- Application of Ferrite Nanoparticles In Wastewater Treatment -- Synthesis of Potassium Niobate (Knbo3) for Environmental Applications -- Nano Magnetite Based Magnetic Glass-Ceramic Obtained from Wastes.
Keywords: Nanotechnology; Ceramic materials; Refuse and refuse disposal; Renewable energy sources; Nanotechnology; Ceramics; Waste Management/Waste Technology; Renewable Energy